Telecom Traffic and Investment in Developing Countries : The Effects of International Settlement Rate Reductions - Wallsten, Scott J. (World Bank, Washington, DC, 2014)
Developing countries, which received about $35 billion in net settlement payments from the United States telecom carriers between 1985 and 1998, were upset by the Federal Communications Commission's (FCC) decision to slash rates, because lower rates mean lower payments. They claim that the payments help finance telecom investment, and that the FCC's decision will therefore harm their telecom sectors. The author uses a panel data set for 178 countries from 1985 to 1998 to test how changes in settlement rates affect telecom traffic and investment. He finds that rates are significantly negatively correlated with traffic, with the greatest effects in the poorest countries. In other words, reduced settlement rates spur telecom traffic from developing countries to the United States. And while there is a statistically significant correlation between settlement payments and telecom revenues in developing countries, he finds no correlation between the payments and the number of telephone mainlines or imports of telecommunications equipment. In short, there is no evidence that the payments are invested in telecom networks.